Differences between species in seed bank and vegetation helps to hold functional diversity in a floodable Neotropical savanna. (16th February 2021) - de Souza, Evaldo B; Bao, Francielli; Damasceno Junior, Geraldo A; Pott, Arnildo
Abstract: Aims: Our objective was to quantify the contributions of the seed bank and the established vegetation to the species composition, functional composition and diversity, and discuss the implications of these differences in regeneration and persistence of floodplain plant communities. Methods: We sampled all ground cover vegetation up to 1.5 m height and seed bank in 25 plots (10 m × 1 m) distributed across five sites in dry and rainy seasons in a periodically flooded savanna in the Pantanal wetland, Brazil. We evaluated the soil seed bank by seedling emergence method. Important Findings: The seed bank species had traits that conferred regeneration to the communities, while persistence traits characterized the vegetation. The seed bank had higher functional richness and lower functional evenness than the vegetation. The existence of different plant traits between seed bank and vegetation allowed the coexistence of species with functionally contrasting persistence and regeneration traits, which may help maintain functional diversity. It may allow the community to be more resilient when dealing with different environmental filters such as drought, fire and flood.